The Green's function for the three-dimensional linear Boltzmann equation via Fourier transform. (18th March 2016) - Machida, Manabu
Abstract: The linear Boltzmann equation with constant coefficients in the three-dimensional infinite space is revisited. It is known that the Green's function can be calculated via the Fourier transform in the case of isotropic scattering. In this paper, we show that the three-dimensional Green's function can be computed with the Fourier transform even in the case of arbitrary anisotropic scattering.